Analisis Penerapan Corporate Social Responsibility (CSR) pada PT. Malea di Tana Toraja - Herianti Tarukla'bi Tandungan; Yohanis L. Ta’dung; Dina Ramba (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to determine the Corporate Social Responsibility implemented by PT. Malea in Tana Toraja. The method in this research uses a qualitative descriptive approach by conducting direct interviews with informants. Data collection begins with observations, observations, interviews and documentation. The results obtained are the Implementation Stages. This stage is the core stage, namely a concrete action or implementation of CSR. In the CSR implementation stage of PT. Malea also has good steps and is quite regular. At this stage there needs to be involvement between the company and the community regarding the implementation of the CSR program that is being implemented. Implementation/Implementation Stage. This stage is the core stage, namely a concrete action or act of implementing CSR. In the CSR implementation stage of PT. Malea also has good steps and is quite regular. At this stage there needs to be involvement between the company and the community regarding the implementation of the CSR program that is being implemented. The involvement of these parties is intended so that the CSR program can be implemented well and on target. Apart from that, the involvement between the company, employees and the community will foster a sense of ownership between each other in the company's existence, so that this CSR program can strengthen the relationship between the board of directors, company employees and the community.